The Evaluation of Economic Forecasts - Harvey, David (1997)
The evaluation of economic forecasts is a substantial and important aspect of economic research, and a considerable part of such evaluation is performed by comparing competing forecasts. This thesis focuses on the development of statistical procedures in order that reliable comparison of contending forecasts can be made.